ANALISIS KESIAPAN GURU AL-QUR’AN HADIS DALAM MENGHADAPI TANTANGAN PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA DI SMP MUHAMMADIYAH 1 BERBAH YOGYAKARTA - Inggi Desyliana; Muhammad Aufakumara Sucipta; Hendro Widodo (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
Teachers are the implementers of an independent curriculum that requires differentiated learning, in order to create students who grow based on the potential possessed by each student. The purpose of the research is to determine the psychological and technical readiness and strategies of teachers of the Qur'an Hadith of SMP Muhammadiyah 1 Berbah in carrying out differentiated learning through an independent curriculum. By using qualitative techniques with the type of case study research, this research will produce descriptive data in the form of written or spoken words from people and observable behaviors. Data for this study were collected through observation, interviews and documentation. The source of the interview with the Qur'an Hadith teacher at SMP Muhammadiyah 1 Berbah Yogyakarta. The results of this study show that, for technical readiness, it requires teacher ability, teacher creativity, communication between teachers, mastery of material to support the needs of students. Furthermore, in terms of teacher psychology, there are necessary aspects, such as courage, confidence, enthusiasm, and good emotions. Teacher strategy is also one of the keys in the running of differentiated learning. Teachers facilitate students according to their needs so that they can perform better, because the differentiated learning process has an impact on students.